2021
DOI: 10.3390/life11111182
|View full text |Cite
|
Sign up to set email alerts
|

Enceladus as a Potential Niche for Methanogens and Estimation of Its Biomass

Abstract: Enceladus is a potential target for future astrobiological missions. NASA’s Cassini spacecraft demonstrated that the Saturnian moon harbors a salty ocean beneath its icy crust and the existence and analysis of the plume suggest water–rock reactions, consistent with the possible presence of hydrothermal vents. Particularly, the plume analysis revealed the presence of molecular hydrogen, which may be used as an energy source by microorganisms ( e.g., methanogens). This could support the possibility that populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 75 publications
3
12
0
Order By: Relevance
“…Our model predicts ranges of steady-state biomass concentrations (Figure 1) given Enceladus conditions that match previous, independent estimates [52, 64, 69] and would be comparable to eutrophic environments on Earth [75] (see Extended Data Table 1). At the upper end of estimated P concentrations, we find ranges of estimates for higher growth efficiencies that match the estimates offered by [69] and [64] for life growing in hydrothermal fluid. Meanwhile, our low energy estimates match the biomass estimate of 10 5 cells/mL from [52].…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our model predicts ranges of steady-state biomass concentrations (Figure 1) given Enceladus conditions that match previous, independent estimates [52, 64, 69] and would be comparable to eutrophic environments on Earth [75] (see Extended Data Table 1). At the upper end of estimated P concentrations, we find ranges of estimates for higher growth efficiencies that match the estimates offered by [69] and [64] for life growing in hydrothermal fluid. Meanwhile, our low energy estimates match the biomass estimate of 10 5 cells/mL from [52].…”
Section: Introductionsupporting
confidence: 82%
“…Here we use multiple modeling approaches all centered around the meta-framework of considering the relative ratios of different elements in an environment as a biosignature. Our chemostat model, which leverages a few free parameters (energetic limits on maximum growth rate, washout rate - see Methods) to calculate steady state cell density as a function of steady state phosphorus concentration, predicted ranges of supportable cell densities comparable to those previously offered for the Enceladus ocean [52, 64, 69] at high phosphate concentrations, but at the low end of the range of phosphate concentrations suggested by Postberg et al [55], we predict lower supportable cell densities - potentially a signature of phosphate limitation at these low concentrations. We used genomic data on methanogenic Archaea to predict the macromolecular composition of an ecosystem comprised of these organisms, and found that our estimated ecosystem N:P ratio matches, within an order of magnitude, the ammonium:phosphate ratio implied by the maximum concentration from Postberg et al [55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations